Perbedaan Sistem Logika Fuzzy Tipe-1 dan Interval Tipe-2 pada Aplikasi Mobile Robot - Ade Silvia Handayani; Andry Meylani; Ciksadan Ciksadan (Annual Research Seminar (ARS), 2017)
This paper presents differences of type-1 with interval type-2 fuzzy logic systems. T1FLS contains three main processes which are fuzzifier, inference engine, and defuzzifier. Whereas in IT2FLS has five contains which are fuzzifier, inference engine, type-reduction, and defuzzifier. The significant difference is on type-reduction, which makes more complex than T1FLS. Each advantages and disadvantages also affect to efficiency and performance of Fuzzy Logic Systems